2013
DOI: 10.1002/jcph.88
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Canagliflozin, a Sodium Glucose Co‐Transporter 2 Inhibitor, in Subjects With Type 2 Diabetes Mellitus

Abstract: This study characterized single-and multiple-dose pharmacokinetics of canagliflozin and its O-glucuronide metabolites (M5 and M7) and pharmacodynamics (renal threshold for glucose [RT G ], urinary glucose excretion ], and 24-hour mean plasma glucose ]) of canagliflozin in subjects with type 2 diabetes. Thirty-six randomized subjects received canagliflozin 50, 100, or 300 mg/day or placebo for 7 days. On Days 1 and 7, area under the plasma concentration-time curve and maximum observed plasma concentration (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
236
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(264 citation statements)
references
References 25 publications
(56 reference statements)
22
236
2
3
Order By: Relevance
“…This indicates that the FDC is bioequivalent to coadministration with respect to either canagliflozin or metformin pharmacokinetics with no effects on its rate and extent of absorption as well as its elimination attributed to the formulation performance factors of the FDC tablet. Canagliflozin pharmacokinetics from administration of FDC and co-administration of individual tablets were consistent with single-and multi-dose pharmacokinetics of canagliflozin alone (50, 100, and 300 mg) in healthy participants and in adults with T2DM that showed C max and AUC increased in a dose-dependent manner across all 3 doses [37,38]. The single-dose pharmacokinetics of metformin observed in the bioequivalent studies are consistent with previously reported studies of metformin alone in healthy participants [39].…”
Section: Citationsupporting
confidence: 88%
“…This indicates that the FDC is bioequivalent to coadministration with respect to either canagliflozin or metformin pharmacokinetics with no effects on its rate and extent of absorption as well as its elimination attributed to the formulation performance factors of the FDC tablet. Canagliflozin pharmacokinetics from administration of FDC and co-administration of individual tablets were consistent with single-and multi-dose pharmacokinetics of canagliflozin alone (50, 100, and 300 mg) in healthy participants and in adults with T2DM that showed C max and AUC increased in a dose-dependent manner across all 3 doses [37,38]. The single-dose pharmacokinetics of metformin observed in the bioequivalent studies are consistent with previously reported studies of metformin alone in healthy participants [39].…”
Section: Citationsupporting
confidence: 88%
“…Subcutaneous ASPC-1 tumors produced in the upper thigh or lower flank of NSG mice were monitored for up to 4 wk during treatment with 30 mg/kg canagliflozin or dapagliflozin. The protocol for SGLT2 inhibitors was the one developed for inhibiting renal SGLT2 in mice and patients with diabetes (27)(28)(29)(30). As a positive control, we included treatment with the anticancer drug gemcitabine.…”
Section: Is Sglt Functional Activity Correlated With Sglt Expression mentioning
confidence: 99%
“…Canagliflozin lowers plasma glucose by promoting urinary glucose excretion, which results in a mild osmotic diuresis that may be associated with a reduction in intravascular volume 6, 7, 8, 9. While the insulin‐independent mechanism of canagliflozin leads to a low inherent risk of hypoglycaemia, the mild osmotic diuresis it causes may be associated with an increased risk of volume–depletion events, including dehydration.…”
Section: Introductionmentioning
confidence: 99%